Respiratory viruses detection among Influenza-like illness (ILI) cases in Lombardy (Northern Italy) during pre- (2018-2019) and SARS-CoV-2 pandemic (2020-2021) winter seasons. (March 2022) - Pellegrinelli, L.; Bubba, L.; Galli, C.; Primache, V.; Anselmi, G.; Delbue, S.; Signorini, L.; Dolci, M.; Binda, S.; Pariani, E.
Abstract : Purpose: To report a descriptive analysis of the virological results of Influenza-like illness (ILI) surveillance, comparing the frequency of detection of respiratory viruses during the pre-pandemic (2018-2019) and SARS-CoV-2 pandemic (2020-2021) winter seasons in Lombardy (Northern Italy). Methods & Materials: From week 46 to week 17 of the following year, nasal-pharyngeal swabs (NPS) collected from ILIs were tested for influenza viruses (IV), RSV, rhinovirus and enterovirus with specific real-time RT-PCR assays. In 2020-2021, SARS-CoV-2 molecular detection was also included. Results: 464 and 446 NPS were collected in 2018-2019 and 2020-2021, respectively. Sex distribution was similar between these two seasons (males: 51.5% vs 47%, P=0.165), while mean age was statistically higher in 2020-2021 (28.2 years [IQR: 40.5] vs. 43.6 years [IQR: 32.6], P<0.0001). ILI incidence was significantly higher in 2018/19 compared with 2020/21 season season (5.4/1, 000 inhabitants vs. 1.9/1, 000 inhabitants, P< 0.0001.ILI cases <15 years were less reported in 2020-2021 than in 2018-2019 season (P<0.0001). Contrary, those >15 years were more reported in 2020-2021 than in 2018-2019 (15-44 years, P=0.008; 45-64 years, P=0.002; ≥65 years, P<0.0001). In 2018-2019, IV and RSV accounted for 55% and 10% of ILIs, whereas in 2020-2021 no circulation of these viruses was observed. Enterovirus detections decreased from 3.4% in 2018-2019 to 0.4% in 2020-2021 (P=0.01), while rhinoviruses were detected at higher frequency in the latter season (8.6% vs. 11.9%, P=0.07). SARS-CoV-2 was detected in 25.3% of NPS in 2020-2021. Conclusion: Since the beginning of the pandemic, non-pharmaceutical measures, including use of face-masks, was massively applied to contrast SARS-CoV-2 spread. This dramatically reduced the incidence of ILI, the circulation of SARS-CoV-2 and other respiratory viruses (such as IV and RSV) transmitted by droplets, but did not reduce rhinovirus detection, which continued to circulate in 2020-2021 season. ILIs surveillance has demonstrated to be able to capture changes in the epidemiology of respiratory viruses and it should be sustained and improved to increase the capture of ILI remained with unknown etiology.